2021
DOI: 10.1111/codi.15895
|View full text |Cite
|
Sign up to set email alerts
|

Is synoptic operative reporting necessary for Crohn's disease surgery? Variability in surgical reports across inflammatory bowel disease referral centres

Abstract: Around 80% of Crohn's disease (CD) patients require an ileocolic resection (ICR) within 10 years of initial diagnosis, with about 50% of the patients developing a postoperative surgical recurrence [1][2][3]. ICR is the most common operation required for medically refractory disease. A number of surgical findings, including length of resected bowel, anastomotic technique/configuration and operative approach, may be associated with long-term outcomes after ICR [4][5][6][7]. Accordingly, the surgical report is a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(9 citation statements)
references
References 25 publications
(30 reference statements)
1
8
0
Order By: Relevance
“…2,13 Our study demonstrated that it was poorly documented, which mirrors the findings of Mujukian et al's study. 6 In our synoptic report, we categorized the extent of mesenteric dissection into pericolic, partial and complete which may better represent the clinical practice as compared with 'high and close'. We included 'any difficulty in mesenteric dissection' to better comprehend the decision made by the surgeon whether it is by choice (as it is a benign disease) or limited by the difficult CD mesentery typically characterized by bulky, thickened, oedematous and friable.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…2,13 Our study demonstrated that it was poorly documented, which mirrors the findings of Mujukian et al's study. 6 In our synoptic report, we categorized the extent of mesenteric dissection into pericolic, partial and complete which may better represent the clinical practice as compared with 'high and close'. We included 'any difficulty in mesenteric dissection' to better comprehend the decision made by the surgeon whether it is by choice (as it is a benign disease) or limited by the difficult CD mesentery typically characterized by bulky, thickened, oedematous and friable.…”
Section: Discussionmentioning
confidence: 99%
“…This component was not assessed in the Mukujian's study. 6 This group of patients is often nutritionally depleted or on high doses of steroids and may not be suitable for primary anastomosis or requires a diverting stoma. An accurate description of the type of stoma will assist subsequent preoperative planning during the reversal of stomawhether contrast imaging-based study or endoscopy assessment is required or feasible to be performed to assess for anastomotic integrity and the remaining colon for any disease activity.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Inclusion criteria for the committee members included evidence of previously published experience in CD surgery guideline development [5] and standardisation of reporting of intraoperative findings in CD [6], training in IBD surgery [7] and dissemination of digital educational content [8]. The committee consisted of 13 members, including a pathologist with expertise in CD.…”
Section: Me Thodsmentioning
confidence: 99%